Evaluation of two transshipment policies in a two-location decentralized inventory system under partial backordering. (October 2018) - Feng, Pingping; Wu, Feng; Fung, Richard Y.K.; Jia, Tao
Highlights: Two transshipment policies are analyzed in a two-location inventory system. Partial backordering is considered. Unique Nash equilibrium for order quantity is proved for each policy. The proposed method can be used to choose a more economical transshipment policy. Abstract: This research investigates the replenishment and transshipment decisions in a two-retailer inventory system with a single selling season. Both emergency lateral transshipment (ELT) and preventive lateral transshipment (PLT) are investigated. ELT satisfies partial backordering. We prove the existence of unique Nash equilibrium for the system under each policy. The results show that the ELT solution is independent of the transshipment price while the PLT solution converges to the newsvendor solution as the transshipment price increases. Numerical analysis is presented to illustrate the advantage of each policy. This study assists retailers in deciding which transshipment policy should be preferred.